Pupils' Reading Comprehension and its Predictors - E L Grigorenko (RUDN Journal of Psychology and Pedagogics, 2012)
In this article, the results of two studies of reading comprehension are presented and discussed. In the first study (n = 502), indicators of reading comprehension of connected text were predicted by indicators of accuracy of single-word reading and phonological indicators that are traditionally used for this purpose. In the second study (n = 1048), indicators of reading comprehension of connected text were predicted by meta-linguistic indicators. This article discusses both sets of findings and draws a parallel between these findings and the results of Russian students in the international comparison programs PIRLS and PISA.